Germany’s Unwillingness to Lead: The Nature and Exercise of its Power, and How its History, Normalization, and Economic Concerns Have Brought About an Existential Crisis and Reluctance to Lead Alone. - Van Son, Ian G. (Tufts Archival Research Center, 2014)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Germany has entered a new era since reunification and the end of the Cold War, and it continues to search internally as well as externally for its new place in Europe and the world. The events of the last five years in particular have made it clear that Germany will be expected to play a greater role in Europe, but is Germany capable and willing to be a leader in Europe and a world power? Germany’s new position of influence has been made possible by its economic power and its increased profile in Europe. Using its influence, Germany has led Europe by acting as a ‘patron state,’ committing resources to the task of leadership and shaping international institutions through a hegemony embedded in those institutions. But the Eurozone crisis has tested the limits of Germany’s patronage and, in isolating it, caused Germany to step back from a larger leadership role. German leadership has been prevented by its history, its normalization and emboldened pursuit of its national interests, its stretched economy and fear of debt, and a domestic existential crisis resulting in an inability to agree on its future. Germany is finding itself uncomfortable with being a patron without greater influence, but also with carrying the sole responsibility of leading Europe. Germany’s strength is built in large part upon its economy, and when it feels that is stretched, it is at risk of losing power and will be more likely to act in its own interests. The Eurozone crisis has seen Germany’s position soften as it caves to pressure from the other countries. Germany has too much invested in Europe to back away from its commitment to integration and working within the international institutions it has helped form, but it will seek burden sharing and leadership assistance in the future. Going forward, Germany will seek to share the burden of leadership and patronage, wishing to retain the project of integration, but not at the economic and reputational cost that it has recently sustained.